2019
DOI: 10.4103/jos.jos_36_17
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic treatment motivation and cooperation: A cross-sectional analysis of adolescent patients' and parents' responses

Abstract: INTRODUCTION: Motivation for orthodontic treatment among adolescents has been linked with patients’ response during treatment. Parents have also been seen to be influencing factors in patient motivation. This study investigates the motivation for orthodontic treatment among patients and their parents/guardians. MATERIALS AND METHODS: Data were obtained from 100 orthodontic children (41 boys, 59 girls), with a mean age of 11.9 years, in the age range of 7–17 years, and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…Unlike findings of the present study, Barbosa et al, found no significant difference between gender and bracket failure (22). Another factor influencing cooperation in orthodontic treatment is the attitude of the patient's parents/guardians toward orthodontic treatment before and during treatment (26). One study reported that fathers had a positive effect on cooperation, which was comparable to findings of the present study.…”
Section: Discussionsupporting
confidence: 63%
“…Unlike findings of the present study, Barbosa et al, found no significant difference between gender and bracket failure (22). Another factor influencing cooperation in orthodontic treatment is the attitude of the patient's parents/guardians toward orthodontic treatment before and during treatment (26). One study reported that fathers had a positive effect on cooperation, which was comparable to findings of the present study.…”
Section: Discussionsupporting
confidence: 63%
“…The additional important findings of the included manuscripts comprised factors referred to as preponderant for adherence to orthodontic treatment including: duration of use of the appliance [ 8 , 14 ], the level of oral health of the patient [ 8 , 21 , 27 ] and attitude of the dentist [ 30 ]. A good relationship between the dentist and the parents was also referred as an important factor [ 2 , 21 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Defined in a large sense, motivation is the set of dynamic factors that determine the behavior of an individual [ 1 ]. Intrinsic or extrinsic motivation produces different effects on the patient’s psyche, depending on their gender and age, temperament traits, and individual personality [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pedodontist or the orthodontist has the task of guiding the small patients towards the appropriate treatment, motivating them to accept it. Praise and encouragement are much more useful than punishment at a young age [ 1 , 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%